A SOLUTION APPROACH TO APPLICATION OF FUNDS PROBLEMS. - Young, Kenneth G. (The Accounting Review, 1963)
Abstract The conventional approach to teaching the preparation of the application of funds statement calls for the use of a columnar worksheet. Included in a worksheet of this nature are comparative balance sheets, the computed monetary changes in the individual statement items, a number of working paper adjustments and finally, extended figures representing funds applied and provided and working capital increases and decreases. The purpose of the worksheet is, of course, to facilitate the preparation of the funds flow statement. It is not an end in itself, but merely the means to produce the finished statement. After several years of employing the worksheet technique, the writer became convinced that there must be a more effective method of introducing the student to the preparation of the funds flow statement. One disturbing aspect of the usual textbook approach to such preparation is the excessive amount of time consumed in completing the worksheet, i.e., in entering the comparative balance sheets, in computing and listing and balancing the net changes therein, in recording all the necessary adjustments and finally, in extending the net changes, as adjusted, to the appropriate statement columns.